Hemorrhagic morbidity in placenta accreta spectrum with and without placenta previa - Mulla, Bethany M. (Arch Gynecol Obstet, 2019)
PURPOSE: The incidence of placenta accreta spectrum (PAS; pathologic diagnosis of placenta accreta, increta or percreta) continues to rise in the United States. The purpose of this study is to compare the hemorrhagic morbidity associated with PAS with and without a placenta previa. METHODS: This was a retrospective cohort study of 105 deliveries from 1997–2017 with histologically-confirmed PAS comparing outcomes in women with and without a co-existing placenta previa. We used the Wilcoxon-rank sum test to compare continuous data and Chi-square or Fisher’s exact test for categorical data. We also performed log-binomial regression to calculate risk ratios adjusted for depth of invasion (aRR) and 95% confidence intervals (CI). RESULTS: We identified 105 pregnancies with PAS. Antenatal diagnosis of PAS was higher in women with coexisting placenta previa (72.3%) than those without (6.9%, p<0.001). Women with co-existing placenta previa had greater median estimated blood loss and more units of packed red blood cells transfused (both p≤0.03). Women with placenta previa were more likely to undergo a hysterectomy (RR: 2.7; 95% CI: 1.8–3.8) and be admitted to the intensive care unit (aRR: 3.3; 95% CI: 1.1–9.6). CONCLUSIONS: Among women with PAS, those with a co-existing placenta previa experienced greater hemorrhagic morbidity compared to those without. In addition, PAS without placenta previa typically was not diagnosed prior to delivery. This study further supports the recommendation for multi-disciplinary planning and assurance of resources for pregnancies complicated by PAS. In addition, our results highlight the need for mobilization of resources for those pregnancies where PAS is not diagnosed until delivery.